Knowledge and practice of problem-based learning: a case of Kasama School of Nursing, Zambia. - Mgbekem MA; Makoleka C (West African Journal of Nursing, 2008)
The study was conducted to assess knowledge and practice of problem-based learning (PBL) among students and staff of Kasama Scbool of Nursing (KSN) Northern Province, Zambia. Stratified and simple random sampling methods were used to select 60 students and 5 staff to participate in the study. Data were collected using a self-administered questionnaire. Responses were analyzed using frequency and percentage and chi-square at 5% level of signifícance. Result showed that there was a significant relationship between knowledge and practice of PBL (X2 cal 32.4) > X2 tab 3.841 at P = 0.05, df 1). It was recommended that more tutors be trained in PBL to help in its facilitation. This method of learning/teaching should be employed in all subjects to enchance learning and practice.